Evolutionary dynamics of repetitive DNA in Semaprochilodus (characiformes, prochilodontidae): A fish model for sex chromosome differentiation - Terêncio, Maria Leandra; Schneider, Carlos Henrique; Gross, Maria Claudia; Vicari, Marcelo Ricardo; Farias, Izeni P.; Passos, Kelmer Batalha; Feldberg, Eliana (Sexual Development, 2013)
Distribution of 6 microsatellites and 5 transposable elements on the chromosomes of Semaprochilodus taeniurus and S. insignis, commonly referred to as Jaraqui, was performed using their physical mapping with fluorescence in situ hybridization. In this study, we aim to understand the evolutionary dynamics in genomes of S. taeniurus and S. insignis by comparing the position, abundance and contribution of the repetitive sequences in the origins and differentiation of a ZZ/ZW sex chromosome system in S. taeniurus. Results revealed that distribution patterns of repetitive DNAs along the chromosomes varied considerably. Hybridization signals were observed on several autosomes in both species; however, in S. taeniurus genome, the repetitive sequences were more abundant. In addition, large clusters of known repetitive sequences were detected in sex chromosomes of S. taeniurus. This observation is notable because the accumulation of repetitive DNAs could reflect the degradation of genetic activities and the differentiation of protosex chromosomes, evolving into the heteromorphic ZW pair observed in S. taeniurus. © 2013 S. Karger AG, Basel.
Keywords: Dna; Microsatellite Dna; Animals; Animals Disease; Animals Model; Characiformes; Chemistry; Female; In Situ Hybridization, Fluorescence; Genetics; Male; Evolution, Molecular; Nucleotide Repeat; Nucleotide Sequence; Sex Chromosome; Sex Differentiation; Transposon; Animal; Base Sequence; Characiformes; Dna; Dna Transposable Elements; Evolution, Molecular; Female; In Situ Hybridization, Fluorescence; Male; Microsatellite Repeats; Models, Animals; Repetitive Sequences, Nucleic Acid; Sex Chromosomes; Sex Differentiation; Characiformes; Prochilodontidae; Semaprochilodus; Semaprochilodus Insignis; Semaprochilodus Taeniurus